2015
DOI: 10.1186/s12938-015-0088-3
|View full text |Cite
|
Sign up to set email alerts
|

On the design of a DEA-based device to pot entially assist lower leg disorders: an analytical and FEM investigation accounting for nonlinearities of the leg and device deformations

Abstract: BackgroundOne of the recommended treatments for disorders associated with the lower extremity venous insufficiency is the application of external mechanical compression. Compression stockings and elastic bandages are widely used for the purpose of compression therapy and are usually designed to exert a specified value or range of compression on the leg. However, the leg deforms under external compression, which can lead to undesirable variations in the amount of compression applied by the compression bandages.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…We envision that this device would rapidly (<1 s) engage, applying 4 pulses at 0-60 mmHg of pressure per minute (4 s on -11 s off). The device might utilize dielectric elastomer actuators (Pourazadi et al, 2015) or shape memory alloys (Moein and Menon, 2014;Moein et al, 2017) to enable intermittent compression, and would contain accelerometers, allowing compression to be activated during motionless standing and deactivated during ambulation (when the skeletal muscle pump helps offset hemodynamic deficits) or during sitting/supine postures (when orthostatic stress is negligible), incorporated into a comfortable and portable garment.…”
Section: Discussionmentioning
confidence: 99%
“…We envision that this device would rapidly (<1 s) engage, applying 4 pulses at 0-60 mmHg of pressure per minute (4 s on -11 s off). The device might utilize dielectric elastomer actuators (Pourazadi et al, 2015) or shape memory alloys (Moein and Menon, 2014;Moein et al, 2017) to enable intermittent compression, and would contain accelerometers, allowing compression to be activated during motionless standing and deactivated during ambulation (when the skeletal muscle pump helps offset hemodynamic deficits) or during sitting/supine postures (when orthostatic stress is negligible), incorporated into a comfortable and portable garment.…”
Section: Discussionmentioning
confidence: 99%
“…Flexible actuators have been widely researched in the auxiliary medical field to achieve controllable compression. For instance, Pourazadi et al . designed an active compression bandage for lower extremity venous insufficiencies, which was based on dielectric elastomer actuators.…”
Section: Applications Of Flexible Actuators In Soft Roboticsmentioning
confidence: 99%
“…a) The calf and its several different regions to closely evaluate the interaction between an active compression bandage and the calf. Reproduced under the terms of the CC‐BY 4.0 License . Copyright 2015, The Authors.…”
Section: Applications Of Flexible Actuators In Soft Roboticsmentioning
confidence: 99%
“…As mentioned above, prior to this work other investigators have reported on the use of DE actuators to develop active bandages [10], [11]. The peculiarities of the approach described here are: 1) two active layers were stacked together to increase the strength of the system; 2) the active layers were made of an acrylic elastomer film showing one of the highest electromechanical transduction performance, in terms of maximum achievable strains and stresses; 3) stiffening sticks were used to maximise actuation along the radial direction; 4) two thick and soft passive layers were used as interfaces with suitable properties in terms of mechanical compliance and electrical safety.…”
Section: Active Bandage Conceptmentioning
confidence: 99%
“…An alternative solution to address these issues comes from the use of Dielectric Elastomer (DE) actuators, which were proven to be effective for interacting with soft bodies [9]. In particular, their use for electro-mechanically active bandages was recently proposed [10], [11]. The device was conceived as a stretchable bandage consisting of a single layer of a silicone elastomer with compliant electrodes on both sides.…”
mentioning
confidence: 99%